Investigating the Efficiency of U.S. Strategies in the War on Terror During George W. Bush's Presidency: Afghanistan as a Case Study - MERAD, Mohammed Dhia; HOUBA, Abdelghani (جامعة الوادي - University of Eloued, 2023)
The study tries to assess the success of American foreign policy in the war against terrorism in Afghanistan during the George W. BUSH administration in terms of time and area. It also highlights the issue of how effective American strategy has been in eliminating terrorism in Afghanistan. The first chapter of this dissertation defines terms related to the issue and covers the historical history of both US and Afghan relations before delving into the strategies utilized by the US in its fight against terrorism in that country. The second chapter discusses the operational parameters of the American campaign in Afghanistan, the methods used to carry it out, and the outcomes of this strategy. It also examines and assesses the success of American foreign policies in the fight against terrorism in Afghanistan. The research employs several methodologies: the historical approach to events, the descriptive approach to describe them, and the analytical approach to evaluating the used strategies and the degree to which they accomplish the programmed aims. The study's findings and recommendations are summarized, with the most significant being that the American war in Afghanistan is one of the longest contemporary conflicts with the greatest number of material losses and human deaths.
Literature and Civilization
Keywords: American Foreign Policy, US Strategies, War on Terrorism.